Analisis Pola Komunikasi Dalam Hubungan Beda Agama Melalui Teori Penetrasi Sosial - Benita, Nadine; Aprillianty, Shabrina (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
A communication strategy in having an interfaith relationship is very necessary, considering that the level of tolerance given to partners is much greater than in relationships of the same faith. Public, legal and family responses are factors that can influence the survival and sustainability of interfaith relations. This research aims in general to find out how the Social Penetration Theory is. To find out how the process of social penetration forms family support and to find out how communication patterns exist between lovers so that they are able to find a way to the relationship they are living. In this research, the author used a qualitative descriptive method with a literature review type or analyzed previous research taken through several existing journals, but it needs to be emphasized that the use of previous journals only serves as reinforcement for this research.